“Naquela manhã fantástica o Rio de Janeiro amanheceu com câncer” (Olhares, 2020)
This paper looks after a gaze over Glauber Rocha and Antônio Pitanga, using the film Câncer as a case study. Making use of Brecht’s formulation, which understands the author as a critic producer, perceptions are raised on the creation and filmmaking process, observing the narratives that are presented by the improvisations during the execution of the scenes. To that end, the text establishes a dialogue with testimonials by Antônio Pitanga (recorded on-line in 2020), an actor of the film Câncer and Glauber’s great fellow. Some considerations of Ismail Xavier, researcher, film critic and professor of cinema, are also highlighted during the discussion.